Utvärdering av radiologiska kriterier för att bedöma tillståndet ileus på hund - von Delwig, Charlotta (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2006)
Dogs presenting with vomiting and abdominal pain, are common patients at the small animal clinic, and the reason for these symptoms can have various aetiologies. One common reason for these symptoms is obstruction of the small intestine caused by a foreign body. Obstruction of the small intestine is best diagnosed by using radiography, contrast-study if needed, and ultrasound. To avoid further examinations, diagnosis from plain radiographs is preferable. One of the signs of illness one can detect from these examinations is a dilation of the small intestine proximal of the obstruction, caused by gas or fluid; ileus. The study of Graham et al (1998) proposed a quantitative measurement for evaluating if a dog has ileus or not. This measurement is a ratio of the diameter of the small intestine, divided by the height of the body of the fifth lumbar vertebra, measured on a lateral projection. Their conclusion was that, using their method, the number 1,6 should be considered upper limit for a normal diameter of the small intestine, with 2,0 as a definite ileus. The ratio 1,6-2,0 was a zone of insecurity. The aim of this study was to decide whether or not small animal clinicians with access to radiography are familiar with, and use, the quantitative measurement that Graham et al have developed for diagnosing ileus in dogs, and to see if there are other methods or diagnostic signs used, that are just as good for this purpose as the method of Graham et al. The results in this study suggests that participants in the study have knowledge of, and use, the quantitative method that this study is evaluating, and that it works quite well.